An Evaluation of Extended Incubation Time with Blind Subculture of Blood Cultures in Patients with Suspect Endocarditis. Issue 3 (1st June 2006) - Forward, Kevin R
Abstract : BACKGROUND: In a small proportion of patients, bacterial endocarditis is due to organisms that grow slowly and may not be recovered in conventional blood cultures incubated for five days. This has led to recommendations for prolonged incubation and routine subculture of negative cultures. OBJECTIVE: The above-mentioned approach is evaluated. METHOD: The microbiology of all blood cultures subjected to prolonged incubation and the charts of individuals who had organisms recovered after five days were evaluated to determine their clinical significance. RESULTS: In all, 507 blood cultures were handled using an extended incubation and blind subculture protocol. Fifty-three blood cultures in 27 patients were positive. Blood cultures were positive after five days in only five cases; patient outcomes were not affected by the results in any of these cases, although several fastidious organisms (ie, Haemophilus paraphrophilus and Haemophilus parainfluenzae ) were recovered in the first five days of incubation. CONCLUSION: Prolonged incubation and blood subcultures in patients with suspected endocarditis or infections due to fastidious organisms do not represent a wise use of increasingly scarce resources.